Русский язык в современной Украине: статус и особенности функционирования с учетом диахронно-синхронного среза - Tatiana Kosmeda (Studia Rossica Posnaniensia, 2016)
The article focuses on analyzing the functioning of the Russian language in Ukraine, including its diachronic and synchronic aspects. The language policy of the Russian Empire, the USSR and modern Ukraine was taken into account in the analysis. The consequences of this language policy, such as Russification, bilingualism, and the mixture of Russian and Ukrainian, are reflected in the new Ukrainian law – “Regulations of State Language Policy”. Pluralism and a new status of Russian as a regional language have also been implemented in this law.